THE EFFECT OF PARTNER READING STRATEGY TOWARD STUDENTS’ READING COMPREHENSION - GLADIS ZHELIN; SITI SUHARSIH; DINA RACHMAWATI (LINGUISTICA, 2024)
Reading is very important; therefore, a good and interesting teaching reading strategy is necessary. The objective of this study was to find out the effect of the use of partner-reading strategy toward students' reading comprehension. The study used quantitative research with quasi-experimental non-equivalent group design. This study used the tenth-grade students of SMKN 1 Kragilan as the population. The groups were put into control and experimental groups; each group consisted of 30 students. The reading test was used as the instrument of this research (pre-test and post-test). The data were analyzed using normality, homogeneity, and hypothesis tests (t-test). Data analysis revealed that the calculated t was higher than the value of t-table from 0.05 level of significance and degree freedom (df) 58 of two-tailed test. That was 3,87 ≥ 2,00. It means that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. It indicated that there was an effect of the use of partner-reading strategy toward students' reading comprehension. From these findings, it can be concluded that partner-reading strategy can be one of reading strategies that can be implemented by the teacher to help students to improve their reading comprehension.